Peran Orangtua dalam Mendukung Keberhasilan Akademik Anak di Sekolah Dasar: Tinjauan Literatur - Irzam, Irzam; Nisa, Sahrun (Lembaga Yasin AlSys, 2024)
Education in elementary school is an important foundation for a child's overall development. This literature review explores the strategic role of parents in supporting children's academic success. Parents play a crucial role through learning assistance, communication with teachers, creating a conducive learning environment, as well as motivation and emotional support. The level of parental involvement is influenced by factors such as background, culture, parenting style, and environmental support. Best practices include partnerships with teachers, learning routines, appreciation, and providing learning resources. Even though there are challenges, opportunities for optimizing parental support can be realized through parent-school-community partnerships, parent training programs, and the use of technology.